Kinetic Model of Biphasic Character of Catalyse Inhibition - Kulys, J.; Kriaučiūnas, K.; Vidžiūnaitė, R. (Nonlinear Analysis: Modelling and Control, 2003)
A mathematical model of kinetics of fungal catalase inhibition with hydroxylamine in presence of substrate (hydrogen peroxide) has been developed. The scheme includes an intermediate formation and slow reversible native enzyme production. The model is based on differential equations of nonstationary kinetics of the enzyme action. The computer simulation was carried out using adaptive Runge-Kuta method.Good satisfactory is achieved if the kinetic constants calculated by modeling nonstationary state of hydrogen peroxide decomposition are used for calculations of inhibition of the catalases at the second phase of inhibition and for kinetics of the intermediate formation, that was determined with stop-flow spectrophotometer.
Keywords: catalase; hydrogen peroxide; hydroxylamine; kinetics; inhibition